Coalition formation - Debraj Ray; Rajiv Vohra (Brown University, Department of Economics, 2013)
This chapter surveys the sizable and growing literature on coalition formation. We refer to theories in which one or more groups of agents (“coalitions”) deliberately get together to jointly determine their actions. The defining idea of a coalition, in this chapter, is that of a group which can coordinate agreements among its members, while it interacts noncooperatively with other non-member individuals and the outside world in general. It is hard to overstate the importance of coalition formation in economic, political and social analysis. Ray (2007) gives several examples in which such a framework comes to life: cartel formation, lobbies, customs unions, conflict, public goods provision, political party formation, and so on. Yet as one surveys the landscape of this area of research, the first feature that attracts attention is the fragmented nature of the literature. The theories that bear on our questions range from collusive behavior in repeated games, to models of bargaining, to cooperative game-theoretic notions of the core, or notions of coalition-proofness in noncooperative games. To unravel the many intricacies of this literature would take far more than a survey. To prevent our terms of inquiry from becoming unmanageably large, we impose a basic restriction.
Keywords: C71; C72; C78; D71; 330; coalition formation; blocking; bargaining; farsightedness; coalition structures; core; stable set